Path apps for box of ramadhan - Teng, Mee Ling; Kasim, Shahreen; Saedudin, Rd Rohmat (Excelligent Academia, 2019)
Map helps to track targeted location but still unable to find actual destination of rural area due to unclear addresses. This problem also faced by owner and members of the Box of Ramadhan when they need to give delivery services to underprivileged people cause low efficiency of service provided. Thus, this project is conducted to design and develop an application called Path Apps for Box of Ramadhan for Android device user to solve problems of reach destination and get related information to reduce overall time spending. Unified Modelling Language diagram used to show the relationship and interaction among all classes. The proposed system is categories into two different interfaces as admin interface and user interface. The application consists of few modules such as login and registration, user list, profile, current location, route, multiple markers and address list and chat modules. Time management, route planning and inventory will be under control by user according to program schedule. This contribute to high efficiency of work.